Coexistence of electrical conductivity and ferromagnetism in a hybrid material formed from reduced graphene oxide and manganese oxide. Issue 11 (20th February 2015) - Murashima, Yusuke; Ohtani, Ryo; Matsui, Takeshi; Takehira, Hiroshi; Yokota, Ryotaro; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract : The coexistence of electrical conductivity and ferromagnetism has been achieved in a reduced graphene oxide and manganese oxide hybrid (rGO–Mn). Abstract : The coexistence of electrical conductivity and ferromagnetism has been achieved in a reduced graphene oxide/manganese oxide hybrid (rGO–Mn) synthesized by chemical reduction of a graphene oxide and Mn 2+ (as its GO–Mn 2+ complex) using hydrazine. The rGO–Mn and GO–Mn 2+ complexes were characterized by Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). In rGO–Mn the Mn was present as manganese oxide nanoparticles located on the rGO nanosheets. This rGO–Mn exhibits both electrical conductivity and ferromagnetism. The synthesis of hybrids incorporating rGO and metal oxides is proposed as a useful strategy for generation of new multifunctional nano-composite materials.